Proteus mirabilis Biofilm: Development and Therapeutic Strategies - Wasfi, Reham; Hamed, Samira M.; Amer, Mai A.; Fahmy, Lamiaa Ismail (Frontiers in Cellular and Infection Microbiology, 2020)
Proteus mirabilis is a Gram negative bacterium that is a frequent cause of catheter-associated urinary tract infections (CAUTIs). Its ability to cause such infections is mostly related to the formation of biofilms on catheter surfaces. In order to form biofilms, P. mirabilis expresses a number of virulence factors. Such factors may include adhesion proteins, quorum sensing molecules, lipopolysaccharides, efflux pumps, and urease enzyme. A unique feature of P. mirabilis biofilms that build up on catheter surfaces is their crystalline nature owing to their ureolytic biomineralization. This leads to catheter encrustation and blockage and, in most cases, is accompanied by urine retention and ascending UTIs. Bacteria embedded in crystalline biofilms become highly resistant to conventional antimicrobials as well as the immune system. Being refractory to antimicrobial treatment, alternative approaches for eradicating P. mirabilis biofilms have been sought by many studies. The current review focuses on the mechanism by which P. mirabilis biofilms are formed, and a state of the art update on preventing biofilm formation and reduction of mature biofilms. These treatment approaches include natural, and synthetic compounds targeting virulence factors and quorum sensing, beside other strategies that include carrier-mediated diffusion of antimicrobials into biofilm matrix. Bacteriophage therapy has also shown successful results in vitro for combating P. mirabilis biofilms either merely through their lytic effect or by acting as facilitators for antimicrobials diffusion.